2013
DOI: 10.1534/genetics.112.149054
|View full text |Cite
|
Sign up to set email alerts
|

Limited RNA Editing in Exons of Mouse Liver and Adipose

Abstract: Several studies have investigated RNA-DNA differences (RDD), presumably due to RNA editing, with conflicting results. We report a rigorous analysis of RDD in exonic regions in mice, taking into account critical biases in RNA-Seq analysis. Using deepsequenced F1 reciprocal inbred mice, we mapped 40 million RNA-Seq reads per liver sample and 180 million reads per adipose sample. We found 7300 apparent hepatic RDDs using a multiple-site mapping procedure, compared with 293 RDD found using a unique-site mapping pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
3
28
1
Order By: Relevance
“…Consequently, improved methods to robustly characterize genome-wide RE events (Danecek et al 2012;Ramaswami et al 2012;Picardi and Pesole 2013) have enabled genome-wide characterization of RE in several, mostly nondiseased, tissues (Danecek et al 2012;Park et al 2012;Lagarrigue et al 2013;Bazak et al 2014;Blanc et al 2014;Han et al 2015). To date, however, only a few studies have reported RE events at a genome-wide scale in disease tissues; for example, Han et al (2015) showed that in various cancer types RE events are associated with survival and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, improved methods to robustly characterize genome-wide RE events (Danecek et al 2012;Ramaswami et al 2012;Picardi and Pesole 2013) have enabled genome-wide characterization of RE in several, mostly nondiseased, tissues (Danecek et al 2012;Park et al 2012;Lagarrigue et al 2013;Bazak et al 2014;Blanc et al 2014;Han et al 2015). To date, however, only a few studies have reported RE events at a genome-wide scale in disease tissues; for example, Han et al (2015) showed that in various cancer types RE events are associated with survival and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, high-throughput RNA-sequencing (RNA-Seq) data were analyzed in multiple studies to identify RNA-DNA mismatches in mammalian mRNAs (Li et al 2011;Bahn et al 2012;Chen et al 2012;Danecek et al 2012;Gu et al 2012;Park et al 2012;Peng et al 2012;Ramaswami et al 2012Ramaswami et al , 2013Dillman et al 2013;Lagarrigue et al 2013). One of the first studies reported a striking list of all 12 types of RNA-DNA differences (RDDs) in human cells (Li et al 2011), while others presented opposing results (Schrider et al 2011;Bahn et al 2012;Danecek et al 2012;Gu et al 2012;Park et al 2012;Peng et al 2012;Ramaswami et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The highly accurate measurement of transcript abundance by RNA-Seq can also be used to discover novel transcripts and to identify alternative splicing isoforms and RNA-editing events (Graveley 2008;Shendure 2008;Bahn et al 2012). In particular, the depth of sequence read coverage per reference nucleotide enhances the qualities of base calling and can improve the large-scale detection of RNA-editing sites (Bahn et al 2012;Peng et al 2012;Lagarrigue et al 2013;Ramaswami et al 2013). Although the alignment of RNA-Seq reads to a reference genome can infer RNA-editing events, distinguishing these from genomeencoded single nucleotide polymorphisms (SNPs) and technical artifacts caused by sequencing or read-mapping errors is still the major challenge in identifying RNA-editing sites using RNA-Seq data (Ramaswami et al 2013).…”
mentioning
confidence: 99%